Measuring atmospheric corrosion with electrochemical noise: A review of contemporary methods. (May 2019) - Ma, Chao; Wang, Zeqing; Behnamian, Yashar; Gao, Zhiming; Wu, Zhong; Qin, Zhenbo; Xia, Da-Hai
Highlights: Atmospheric corrosion is detected and quantified with an electrochemical noise (EN) technique. EN detection system includes an electrode system of probes/sensors and a test equipment system. Different electrode systems are compared. Approaches to data processing and to the solution of potential problems are reviewed. Abstract: Atmospheric corrosion is the most common cause of the deterioration of metallic materials. Effective monitoring of atmospheric corrosion provides scientific basis for understanding its underlying mechanisms. Atmospheric corrosion in metallic materials can be detected and quantified with an electrochemical noise (EN) technique that includes an electrode system of probes/sensors and a test equipment system. Different electrode systems are compared, and approaches to data processing and to the solution of potential problems are reviewed.